Effects on Bone Repair of Osteotomy With Drills or With Erbium, Chromium: Yttrium‐Scandium‐Gallium‐Garnet Laser: Histomorphometric and Immunohistochemical Study. Issue 4 (1st April 2016) - Esteves, Jônatas Caldeira; de Souza Faloni, Ana Paula; Macedo, Paula Delello; Nakata, Patrícia Borges; Chierici Marcantonio, Rosemary Adriana; Intini, Giuseppe; Marcantonio, Elcio
Abstract : Background: The erbium, chromium:yttrium‐scandium‐gallium‐garnet (Er, Cr:YSGG) laser has been widely used in the dental clinic; however, few studies have demonstrated the advantages of the use of this laser for bone osteotomies. The purpose of this study is to evaluate and compare the bone repair process of defects generated by the Er, Cr:YSGG laser or conventional drills. Methods: Ninety‐six rats were divided into two groups of 48 animals (drill group and laser group). After surgical exposure of the right tibia, the animals were subjected to a 2‐mm‐diameter osteotomy created by conventional drills (drill group) or by the Er, Cr:YSGG laser (laser group). The animals were sacrificed 0, 3, 7, 14, 30, and 60 days after the creation of the defect, and histologic sections were obtained and used for histomorphometric and immunohistochemical analyses for the detection of osteocalcin, osteoprotegerin, receptor activator of nuclear factor κ‐B ligand, vascular endothelial growth factor, and caspase‐3. Results: The osteotomy with the drill produced well‐delimited and smooth walls, whereas the osteotomies in the laser group were irregular and presented an amorphous basophilic line and bone necrosis that was slowly resorbed during the repair process. Despite these characteristics, bone repair was similar between groups at various time points, and, at 60 days, the defects in both groups were completely repaired by newly formed bone. Conclusion: The repair process of osteotomies created by the Er, Cr:YSGG laser, despite producing thermal damage to bone tissue, is comparable to that with conventional drills.